The Transnational Experience of a Chinese Buddhist Master in the Asian Buddhist Network - Zhang, Xing (Religions, 2023)
Wuqian (1922–2010) was one of the most important modern Buddhist masters in the modern history of Sino-Indian Buddhist relations. In his early years, he studied all the major schools of the Buddhist tradition, focusing on Yogācāra philosophy, probably due to Xuanzang’s influence and in alignment with contemporary Buddhist trends. Furthermore, he became one of the few masters from the Central Plains who received systematic training in Tibetan Buddhist tantric rituals. He went to India in the middle of the 20th century. He dedicated his life to the revival of Buddhist thought in India, especially promoting Chinese Buddhism in Calcutta by establishing Buddhist institutions, managing Buddhist sites, organizing Buddhist activities, and building the Xuanzang Temple. In his later years, he devoted himself to facilitating mutual Buddhist exchanges and monastic visits between Buddhist organizations in mainland China, Taiwan, and India. In 1998, he presented two Buddhist relics to the Daci’en Temple in Xi’an. At the beginning of the 21st century, he established the Institute of Buddhist Studies at Xuanzang Temple in Calcutta. He organized the translation of many important Buddhist treatises, again reflecting his intention of following the spirit of Xuanzang to contribute to Chinese Buddhism. His transnational journey manifested that there was an active Asian Buddhist network during the Cold War era, despite various difficulties.